The reading of extended text in Oshindonga in grade 2 in selected Namibian schools - Ngula, Elizabeth Njanjukweni-Aluhe (Rhodes University, Faculty of Education, Department of Education, 2011)
This study was conducted in order to understand to what extent Grade 2 teachers use books (or other forms of extended text) in their reading lessons in Oshindonga where very little published material is available, and, if so, whether they engage in shared reading with these materials or not. The study also explored ways to introduce more books (or other forms of extended text) into Oshindonga classrooms. The study took the form of an interpretive case study. It was conducted in two primary schools in Otjiwarongo district in the Otjozondjupa region of Namibia. Two qualified Grade 2 teachers were selected. The purpose of this sampling was to gain an in depth understanding of how these two selected teachers taught reading in Oshindonga. The data was gathered by using semi-structured interviews with open-ended questions, as well as lesson observations and stimulated recall with each individual teacher after each lesson. The purpose of this was to gain clarity in areas that were not clear during lesson presentations. A focus group interview was also conducted in order to generate ideas about how to introduce more extended texts into the classroom. The key fmdings are that both schools in the study lacked books in Oshindonga, and the teachers lacked an understanding of the importance of using books (or other forms of extended text). Other key findings are that teachers had a problem in choosing appropriate texts to read with their learners; teachers understand reading more as decoding than reading for meaning and pleasure; children were not asked any comprehension questions and the two teachers had different views on the value of shared reading. The research data revealed that there are problems in teaching literacy in Namibian African languages.
Keywords: Ndonga language -- Study and teaching -- Namibia; Reading comprehension -- Study and teaching (Primary) -- Namibia; Reading (Primary) -- Namibia; Teaching -- Namibia; Teachers -- Attitudes -- Namibia; Literacy -- Namibia